Pengaruh Kinerja Pegawai Kelurahan terhadap Kepuasan Masyarakat di Kelurahan Nginden Jangkungan, Surabaya - Ismi Erli Syephiana; Anggraeny Puspaningtyas; Yusuf Hariyoko; Joko Widodo (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Employee performance in government agencies often gets a red report card from the public. These problems usually arise as a result of employee performance that is considered unsatisfactory to service users such as not being able to explain service procedures, unprofessional time management and lack of providing solutions to problems encountered. The assessment of employee performance as described by Andrew states; Quantity, Quality, Job knowledge and employee skills in carrying out work are one of the assessments of good performance on employees. The level of public satisfaction is influenced by the performance of employees and in this era of bureaucratic reform is very well considered by the government. The government through the Minister of Administrative Reform and Bureaucratic Reform issued Permenpan No.14 of 2017 which explains the guidelines for community satisfaction surveys in public service delivery units. The purpose of this study was to analyze the effect of village employee performance on community satisfaction in Nginden Jangkungan Village, Surabaya. The method used in this research uses quantitative methods. The population used is the people of Nginden Jangkungan Village using a sample based on the slovin formula which obtained the results of 105 respondents. The technique used in analyzing this research is simple linear regression. In processing the respondent's data, the author uses the SPSS version 26 system and produces an answer which states that the performance variable partially and significantly affects community satisfaction in Nginden Jangkungan Village, Surabaya. Then based on the simultaneous test, the performance variable of Nginden Jangkungan Village employees also has a positive and significant effect on community satisfaction. The conclusion of this study is that there is a significant and positive effect of urban village employee performance on community satisfaction. However, it is necessary to pay attention to the officer's ability to manage time management and responsibility because it is slightly lagging behind other statement items.